Impact of Landfills on Soil Contamination by Some Heavy Metals at Kani-qrzhala in Erbil City- Iraqi Kurdistan Region - Ismaeel T. Ahmed; Yaseen Gh. Hamad (Zanco Journal of Pure and Applied Sciences, 2023)
The present study was carried out in November 2019 to investigate the impact of Kani-qrzhala landfill on soil pollution of the surrounding area caused by the disposed of refuses from houses, factories, and hospitals. Soil samples were collected from 6 sites in Kani-qrzhala landfill on Erbil-Mosul Road ((Latitude 36˚13̍ N, Longitude 43˚.58̍̍ E). Soil samples were taken randomly selected at different depths (0-10), (10-20), (20-30) cm, were collected randomly at the dumpsite field in the study area with a control sample. The different parameters of soil samples were analyzed of contaminated metals such as Iron (Fe), Manganese (Mn), Nickel (Ni), Lead (Pb), and Zinc (Zn) were determined in the study soil samples by using portable x-ray fluorescence (XRF). Additionally, specialization index Geoaccumulation (I geo) was calculated and used for evaluating the soil pollution status: In the depth (0-10) cm, the heavy metals concentration was recorded as follow: Fe > Pb > Zn > Ni > Mn. Also in the depth (10-20) cm Fe > Pb > Zn > Mn > Ni. In the depth (20-30) cm depth Fe > Pb > Mn > Zn > Ni (0 mg kg-1). Measuring Geoaccumulation index (I geo): The results show that most the most location of the study area of soil surrounding the dumpsite were polluted by heavy metals followed by series: Ni, Pb > Zn > Fe >Mn.